МЕТОДИ ЕКСПЕРИМЕНТАЛЬНИХ ДОСЛІДЖЕНЬ ХАРАКТЕРИСТИК ТВЕРДОГО РАКЕТНОГО ПАЛИВА - VASYLIV, S. S. (текст 3, 2026)
DOI: https://doi.org/10.15407/itm2026.01.034 The process of designing a solid-propellant rocket engine is a complex problem. Usually, it is solved by an iterative method, in which the initial data are gradually refined using experimental studies. With a sufficient statistical database, the problem is somewhat simplified because use can be made of the results for a similar engine close to that under development. In any case, the design is completed by engine testing. The cost of each stage depends on the complexity of the engine as a whole, but the most expensive stage is always the engine testing. Because of this, in order to minimize resources, rocket engine developers try to reduce the extent of experimental tryout. In addition to energy characteristics, an important parameter necessary for engine design is the propellant combustion characteristics. The solid rocket propellant burning rate depends on many factors: the propellant type and initial temperature, the combustion chamber pressure, the component particle size, the flight acceleration, the gas speed near the charge surface, etc. Accordingly, these properties are used to regulate the burning rate. Since it is now mathematically very difficult to predict the solid rocket propellant burning rate, various experimental methods are used for these purposes. The goal of the work is to analyze experimental methods of solid rocket propellant characterization at the research stage. Research tests are carried out to study working processes occurring in the engine and its systems. Their study is necessary for the development and use of new propellants, radically new design ideas, and advanced materials and technologies. Research test programs are diverse and usually require new test and measurement methods and means. Therefore, this stage of rocket engine development is more often carried out using not standard equipment, but unique experimental installations or models, which allow one to obtain information on the object of research with a certain degree of reliability. The primary objectives of experimental studies at the research stage are to characterize the propellant and its combustion process to a required accuracy. This article overviews the most widely used methods for solid rocket propellant characterization. REFERENCES 1. Garbinets V. O., Gorbenko G. A., Gumnytsky B. P., Dzhur O. Ye., Kuchma L. D., Pron L. V. Fundamen-tals of Solid-Propellant Rocket Engine Theory and Design. Art-Press, 2005. 200 pp. (In Ukrainian). 2. Rogov N. G., Ishchenko M. A. Mixed Solid Rocket Propellants: Components. Requirements. Proper-ties. St. Petersburg: St. Petersburg State University of Technology, 2005. 195 pp. (In Russian). 3. Suprunenko V. A. Experimental Tryout Organization of Large-Sized Sustainer Solid-Propellant Rocket Engines. Dnipropetrovsk: Yuzhnoye State Design Office, 2000. 38 pp. (In Russian). 4. Gladkov I. M., Ermakov Yu. P., Malkin B. Ya. Mukhamedov V. S., Nalivaiko V. A., Soloukhin A. S. Solid-Propellant Pulse-Type Special-Purpose Engines. Design Fundamentals, Design, and Tryout Experience. Moscow: Central Research Institute of Information, 1990. 116 pp. (In Russian). 5. G. Gupta, L. Jawale, Mehilal, B. Bhattacharyа. Various methods for the determination of the burning rates of solid propellants - An overview. Central European Journal of Energetic Materials. 2015. V. 12. No. 3. Pp. 593-620. 6. Wei W., Yan X., Cui J., Wang R., Zheng Y., Xue C. Ultrasonic signal processing method for dynamic burning rate measurement based on improved wavelet thresholding and extreme value feature fitting. Micromachines. 2025. V. 16. 290. https://doi.org/10.3390/mi16030290 7. Oatman S. A., Caito A. A., Klinger D. J., Cooper J. N., Manship T. D., Son S. F. Closed vessel burning rate measurements of composite propellants using microwave interferometry. Propellants, Explosives, Pyrotechnics. 2024. V. 49. Iss.8. e202400072.https://doi.org/10.1002/prep.202400072 8. Trebinski R., Leciejewski Z. Surma Z. determining the burning rate of fine-grained propellants in closed vessel tests. Energies. 2022. V. 15. Iss. 7. 2680.https://doi.org/10.3390/en15072680 9. Razdan M.K., Kuo K. K. Erosive Burning Studies of Composite Solid Propellants by the Reacting Tur-bulent Boundary-Layer Approach. The Pennsylvania State University. 1976. 82 рp. 10. Liu J., Wang Y., Li X., Cong J. Using the impulse method to determine high-pressure dynamic burn-ing rate of solid propellants. Aerospace. 2023. V. 10. 818.https://doi.org/10.3390/aerospace10090818 11. Proroka V. A., Solntsev V. A., Kulyk O. V., Dobrodomov O. O., Shvets A. S., Lukianenko I. H., Dron M. M. Verification of methodological approaches to evaluating the characteristics of composite solid rocket propellants. Journal of Rocket-Space Technology. 2024. V. 33. No. 4-29. Pp. 11-22. (In Ukrainian). https://doi.org/10.15421/452446 12. DeLuca L. T., Annovazzi A. Survey of burning rate measurements in small solid rocket motors. Fire-PhysChem. 2024. V. 4. Iss. 2. Pp. 146-165. https://doi.org/10.1016/j.fpc.2023.11.004